Modelling of packed bed and coated wall microreactors for methanol steam reforming for hydrogen production - Hafeez, Sanaa; Aristodemou, Elsa; Manos, George; Al-Salem, Sultan M.; Constantinou, Achilleas (My University, 2020)
A Computational Fluid Dynamics (CFD) study has been conducted to assess the performance of packed bed and coated wall microreactors for the steam reforming of methanol with a CuO/ZnO/Al2O3 based catalyst (BASF F3-01). The results obtained were compared to experimental data from the literature to assess the validity and robustness of the models, and a good validation has been obtained. The performance of the packed bed and coated wall microreactors is similar at a constant reforming temperature. It was found that methanol conversion is enhanced with increasing temperature, residence time, steam to methanol ratio, and catalyst coating thickness. Furthermore, internal and external mass transfer phenomena were investigated using the models, and it was found that there were no internal and external mass transfer resistances for this reactor configuration. Further studies demonstrated that larger catalyst pellet sizes led to the presence of internal mass transfer resistance, which in turn causes lower methanol conversions. The CFD models have exhibited a sound agreement with the experimental data, hence they can be used to predict the steam reforming of methanol in microreactors.
Keywords: Catalysts; Chemical reactors; Computational fluid dynamics; Copper oxides; Hydrogen production; Mass transfer; Methanol; Packed beds; Steam; Thickness measurement